Analisis Validitas Lembar Kerja Peserta Didik Biologi Terkait Keterampilan Berpikir Kritis Peserta Didik SMP - Mili Yana; Muhammad Zaini; Dharmono Dharmono (Wahana-Bio: Jurnal Biologi dan Pembelajarannya, 2022)
Critical thinking skills are needed in 21st century learning. Learning tools must be prepared by the teacher to improve students' critical thinking skills. Student worksheets (LKPD) are one of the learning tools that can train higher-order thinking skills. LKPD can be used to train all cognitive and experimental aspects, so the development of LKPD needs to be done. LKPD development is carried out using the Tessmer model up to the expert review stage. This study aims to describe the feasibility of product development. Validity was carried out by three experts on the aspects of content feasibility, language, presentation, and graphics. The validity value of LKPD shows a very valid category in all three aspects. The product is feasible to continue in the next test.